EFFECT OF AZADIRACHTA INDICA ON THE HEPATO-RENAL FUNCTIONS IN BROILERS CHICKENS - Z. Jawad; M. Younus; M. U. Rehman; R. Munir; A. Maqbool; W. Shahzad; S. Masood; K. Muhammad (Journal of Animal and Plant Sciences, 2014)
Most of the commercial poultry growers use antibiotics for growth promotion and to many disadvantages like higher rearing cost, adverse side effects on health of birds, prolonged withdrawal period and residual effects. Some plants and their extracts improve feed intake and enzymatic activity of the birds. A few of these herbs have antimicrobial, Coccidiostatic or anthelmintic effects. A study was conducted at University of Veterinary and Animal Sciences (UVAS), Lahore to see the effects of neem (azadirachta indica) on the hepato-renal functions in broilers chickens. Experiment was conducted on 144 day old commercial broilers chickens for a period of 42 days.  The birds were equally divided into three groups; A, B and C with 48 chicks in each group. Each group was further subdivided into four subgroups with 12 birds in each subgroup. Dry neem leaf powder was added in feed of birds @ 2 grams/kg (A1, A2, A3); 4grams/kg (B1, B2, B3) and 6 grams/kg (C1, C2, C3). Subgroups A1, B1and C1were treated from 0-42 days of their life; subgroups A2, B2and C2 were fed with the herb from14-42 days, whereas subgroups A3, B3and C3 were given neem leaves from 28-42 days. Birds of subgroups A4, B4 and C4 were kept as untreated controls. On 42nd day, significantly (p<0.05) decreased serum alkaline phosphatase (ALP) and aspartate aminotranferase (AST)  levels were recorded in birds  of subgroups A1, B1, and C1 as compared to other subgroups within their respective main groups. Serum creatinine and especially serum uric acid values showed a decreasing trend with increased level of neem leaf meal. It was concluded that azadirachta indica at limited dose rate might be used as hepatoprotecter in commercial poultry without any toxic effects and it was also concluded that proteins in the diets were more effectively utilized in the neem treated birds.
Keywords: azadirachta indica; growth promoter; commercial poultry; serum alkaline phosphatase (ALP) serum aspartate aminotransferase (AST); serum creatinine and serum uric acid